The Passenger Satisfaction Survey in the Regional Integrated Public Transport System - Valaskova, Martina; Križanova, Anna (Promet - Traffic&Transportation, 2008)
This article describes the Quality criteria Method of the Servicesin the Integrated Public Transport System in Slovak Republic.The proposed method is based on the detailed list of theQuality criteria of the Services in Public Transport from theview of passengers. The criteria are determined based on theSlovak Technical Norm STN EN 138 16 which is related toquality of transport. The method has been applied in RegionalIntegrated Public Transport System of Zilina (ZRIDS) in theform of Passenger Quality Satisfaction Survey.